The Phenomenological Counter-intentionality of the Icon: Jean-Luc Marion’s Reception of Nicholas of Cusa’s Eicona Dei - Pizzi, Matías Ignacio (2023)
The main goal of this paper is to show Nicholas de Cusa´s influence on the notion of Icon (icône) as counter-intentionality in Jean-Luc Marion’s phenomenology of givenness. In order to do this, first, we offer a study of the early conception of Icon in Marion, as it appears in L’Idole et la distance (1977) and Dieu sans l’être (1982), showing the passage from an early conception of the icon to its first phenomenological formulation. As we will see, in this early period there is already an influence of the christian neoplatonic tradition (Dionysius the Areopagite). Secondly, we analyze the reception practiced by Marion of the Nicholas of Cusa’s thought. In this case, we indicate specifically how the Cusanian notion of eicona dei appears as a fundamental historical antecedent of the Icon as a saturated phenomenon, thus revealing the importance of Christian Neoplatonism in the phenomenology of givenness.